Self-Control and Youth Moral Crisis: An Analysis of QS. Yusuf 23–25 Based on Tafsir Al-Misbah - Muhammad Idris Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
This study examines the moral framework of self-control in QS. Yusuf 23–25 based on the exegetical insights of Tafsir Al-Misbah, with a particular emphasis on its relevance to the contemporary moral crises experienced by youth. Employing a tahlili method, the analysis focuses on the textual meaning of each verse and its contextual interpretation as articulated by tafsir Al-Misbah. The findings indicate that the passage highlights four core ethical imperatives: patience as deliberate restraint of desire, responsibility as moral awareness of consequences, steadfastness as loyalty to divine moral order, and avoidance of illicit relationships as a preventive ethical discipline. These principles collectively suggest a Qur’anic model of self-control that is both spiritually grounded and socially relevant. The study concludes that the Yusuf narrative offers a robust moral ontology capable of informing youth character development and addressing contemporary ethical disruptions within a modern sociocultural landscape.